Desperately seeking a duchess - Caldwell, Christi (Caldwell, Christi. All the duke's sins, 2022)
What happens when an impoverished duke with a reputation for being a rogue collides with a strong-willed heiress who wants to explore the world? An unlikely friendship...and unexpected passion.